The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0066-782x2007001500009
|View full text |Cite
|
Sign up to set email alerts
|

Ativação imune-inflamatória na insuficiência cardíaca

Abstract: as from indirect costs related to the reduction in the quality of life and to productivity loss [1][2][3] . Two million Brazilians are currently estimated to live with HF, and up to one third of hospital admissions in the Brazilian public health system are estimated to result from this disease 2,3 ; moreover, among patients older than 60 years of age, HF is the major cause of hospital admissions and mortality in Brazil and in the rest of the Western world 1,3 . The epidemiological setting seems to be even more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…The form chosen to analyze TNF-α was the measurement of s-TNFr1 because TNF-α has a short half-life and may be more unstable in the blood stream when compared with the soluble receptors [3]. The sTNFr1 mediates the most part of the actions of TNF-α, and it has already been demonstrated that this soluble receptor is a more reproducible marker and an indicator that reflects better the action of TNF-α, and thus, the inflammatory activity [3].…”
Section: Blood Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The form chosen to analyze TNF-α was the measurement of s-TNFr1 because TNF-α has a short half-life and may be more unstable in the blood stream when compared with the soluble receptors [3]. The sTNFr1 mediates the most part of the actions of TNF-α, and it has already been demonstrated that this soluble receptor is a more reproducible marker and an indicator that reflects better the action of TNF-α, and thus, the inflammatory activity [3].…”
Section: Blood Analysismentioning
confidence: 99%
“…The sTNFr1 mediates the most part of the actions of TNF-α, and it has already been demonstrated that this soluble receptor is a more reproducible marker and an indicator that reflects better the action of TNF-α, and thus, the inflammatory activity [3].…”
Section: Blood Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the deteriorative changes involved in the progression of HF, which were previously interpreted as arising from changes in salt and water retention or changes in hemodynamic parameters, have been described as recurring processes that culminate in local and systemic inflammatory activation [5][6][7][8][9] , which can be evidenced by the increase in the gene expression and the production of proinflammatory cytokines, such as tumor necrosis factor α (TNF-α); interleukins 1β (IL-1β), 6 (IL-6) and 18 (IL-18 ); cardiotropin-1; CC and CXC chemokines, among other inflammatory markers, in plasma, muscle-skeletal and heart, as well as in peripheral lymphocytes of rats and HF patients. In addition to contributing to the pathophysiology and the progression of structural and functional changes in the heart muscle, these inflammatory mediators may directly lead to peripheral manifestations of the HF syndrome, especially in those changes related to a decrease in muscle mass and functional changes 10,11 , among others.…”
Section: Introductionmentioning
confidence: 99%